2014
DOI: 10.4103/0970-9290.152182
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Propolis and Xylitol chewing gums on salivary Streptococcus mutans count: A clinical trial

Abstract: Propolis chewing gum can be used as an anticariogenic agent in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…8,9,26,27 Previous studies have reported the strong antimicrobial activity of propolis against several bacteria of the oral m icrobiome, i ncludi ng S. mutans. 1,2,28,29,30,31 As confirmed in our study, propolis and some of its isolated compounds, such as apigenin and tt-farnesol, 11 have been found to display a major effect on microbial virulence (e.g., polysaccharide production and acid tolerance), rather than affecting unspecific or specific microbiome viability, considered a highly desirable quality.…”
Section: Discussionmentioning
confidence: 51%
“…8,9,26,27 Previous studies have reported the strong antimicrobial activity of propolis against several bacteria of the oral m icrobiome, i ncludi ng S. mutans. 1,2,28,29,30,31 As confirmed in our study, propolis and some of its isolated compounds, such as apigenin and tt-farnesol, 11 have been found to display a major effect on microbial virulence (e.g., polysaccharide production and acid tolerance), rather than affecting unspecific or specific microbiome viability, considered a highly desirable quality.…”
Section: Discussionmentioning
confidence: 51%
“…Previous research has been established that caries prevalence was not significantly different in boys and girls at an average age ( 17 ). Literature has shown a positive co-relation between baseline S. mutans count and DMFT/dmft ( 18 - 21 ), therefore in our study subjects with DMFT/dmft > 3 were included. Children with special health care needs, systemic diseases, current or recent use of antibiotics and undergoing any dental treatment, orthodontic treatment were excluded from the study since these conditions may alter the microbial load in the oral cavity ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other ingredients incorporated in chewing gum such as chlorhexidine, chitosan, magnolia bark extract, mastic, and propolis were also shown to lower the concentration of planktonic bacteria in saliva compared to a control gum [86,[93][94][95][96][97].…”
Section: Effects On Planktonic Bacteria In Salivamentioning
confidence: 98%